Inhibition of glutamine synthetase by phosphinothricin leads to transcriptome reprograming in root nodules of Medicago truncatula - Seabra, Ana R (2016)
Glutamine synthetase (GS) is a vital enzyme for the assimilation of ammonia into amino acids in higher plants. In legumes, GS plays a crucial role in the assimilation of the ammonium released by nitrogen-fixing bacteria in root nodules, constituting an important metabolic knob controlling the nitrogen (N) assimilatory pathways. To identify new regulators of nodule metabolism, we profiled the transcriptome of Medicago truncatula nodules impaired in N assimilation by specifically inhibiting GS activity using phosphinothricin (PPT). Global transcript expression of nodules collected before and after PPT addition (4, 8, and 24 h) was assessed using Affymetrix M. truncatula GeneChip arrays. Hundreds of genes were regulated at the three time points, illustrating the dramatic alterations in cell metabolism that are imposed on the nodules upon GS inhibition. The data indicate that GS inhibition triggers a fast plant defense response, induces premature nodule senescence, and promotes loss of root nodule identity. Consecutive metabolic changes were identified at the three time points analyzed. The results point to a fast repression of asparagine synthesis and of the glycolytic pathway and to the synthesis of glutamate via reactions alternative to the GS/GOGAT cycle. Several genes potentially involved in the molecular surveillance for internal organic N availability are identified and a number of transporters potentially important for nodule functioning are pinpointed. The data provided by this study contributes to the mapping of regulatory and metabolic networks involved in root nodule functioning and highlight candidate modulators for functional analysis.